Changes in cardiovascular risk factors among adolescents from 1995 to 2004 in the Republic of Karelia, Russia - Rogacheva, Anastasiya; Laatikainen, Tiina; Tossavainen, Kerttu; Vlasoff, Tiina; Panteleev, Vladimir; Vartiainen, Erkki (The European Journal of Public Health, 2007)
Background : In Russia, cardiovascular mortality is among the highest in the world. Behaviours related to the development of cardiovascular disease are usually adopted in childhood and adolescence. Very little information exists on prevalence and trends of risk factors among Russian youth. This study aims to investigate changes in the prevalence of cardiovascular risk factors among adolescents in the Republic of Karelia, Russia, from 1995 to 2004. Methods : Cross-sectional surveys on chronic disease risk factors were carried out among 15-year-old adolescents in Pitkäranta region, in the Republic of Karelia. The surveys were conducted in all 10 secondary schools in the Pitkäranta region. All ninth-grade students in 1995 ( N = 385, response rate 95%) and in 2004 ( N = 395, response rate 85%) were included in the survey samples. Results : Systolic blood pressure decreased statistically significantly among boys (from 119 to 116 mmHg). Diastolic blood pressure decreased statistically significantly among both girls (from 64 to 59 mmHg) and boys (from 62 to 59 mmHg). Total cholesterol increased statistically significantly only among girls (from 3.9 to 4.1 mmol/l). Body mass index did not exhibit any significant changes in both genders. Daily smoking rate doubled statistically significantly among girls from 7% to 15%. Conclusion: The study results show changes in the prevalence of cardiovascular disease risk factors among adolescents in the Republic of Karelia occurring over the last decade. Active measures need to be taken to prevent the increase in smoking prevalence, especially among girls, and to avert the unfavourable development of other risk factors in the future.